The Effect of Exposure Length to Jazz Music on The Production of Pakcoy (Brassica Rapa, L) in Indoor Cultivation - Tamba, Devi Suharni; Wijaya, I Made Anom Sutrisna; Arthawan, I Gusti Ketut Arya (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 10 No 2 (2022): SeptemberDO - 10.24843/JBETA.2022.v10.i02.p18, 2021)
The photosynthesis process in indoor cultivation system does not get optimal sunlight, therefore LEDs can be used as artificial light. The red-blue color is a color that has a positive effect on plant growth. In addition, to increase the rate of photosynthesis, one of the technology advances that can be used is sonic bloom. Sonic bloom is the delivery of high-frequency sound waves in plants to stimulate the opening of the leaf stomata mouths which is accelerating the rate of absorption of carbon dioxide, water and soil minerals. In this study, Pakcoy was exposed to jazz music to determine the effect on production of Pakcoy, and the best length of exposure. The length of exposure to jazz music was 1 hour, 2 hours, 3 hours, 4 hours, and 5 hours starting from 07.00 WITA. The type of jazz music used was Jazz Rock with the musical instrument Gambandella by Psychedelic Jazz-Rock Fusion with a frequency of 86 – 21189 Hz and a sound intensity of 65-95 dB. In the growth chamber, artificial light red-blue LED was used with a light intensity of 1900 – 2100 Lux. The results showed the length of exposure to jazz music significantly affected the production of Pakcoy. The exposure length of 5 hours showed the best result ??(fresh harvest weight 55.49 gs, root wet weight 2.18 gs, and biomass 2.95 gs). In conclusion, exposure length to jazz music has a positive effect on Pakcoy production.